2016
DOI: 10.1007/s00784-016-1766-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of remnants of sealants left behind in pits and fissures of occlusal surfaces after 2 and 3 years

Abstract: ObjectivesThe null-hypothesis tested was that there was no difference in the frequency of remnants of high-viscosity glass-ionomer sealants left behind in pits and fissures of occlusal surfaces of first permanent molars and that of resin composite and glass-carbomer sealants.Materials and methodsBased on the results of a sealant trial, a sample of sealed teeth from which the material had apparently completely disappeared from at least one of the three sections into which the occlusal surface was divided, asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…22 On the other hand, another study concluded that the frequency of Glass Carbomer sealant remnants in pits and fissure is not lower than those of glass ionomer or resin sealants. 23 The reason for this disagreement may be due to the difference in the observation period. In our study, the overall observation period was 12 months, while in their study, the observation period extended for 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…22 On the other hand, another study concluded that the frequency of Glass Carbomer sealant remnants in pits and fissure is not lower than those of glass ionomer or resin sealants. 23 The reason for this disagreement may be due to the difference in the observation period. In our study, the overall observation period was 12 months, while in their study, the observation period extended for 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…From these, six papers were excluded due to different reasons: in vitro studies, 24,25 non-randomized trial, 26 cost-effectivity study 27,28 prevention of carious lesions in permanent molars with micro-cavities in dentin. 29 One project of clinical trials, registered at the Dutch Trial Registration Centre (# 1441), resulted in 6 different papers [19][20][21][22]30,31 that showed data from distinct follow-up periods and outcomes. They were combined to describe the study characteristics, the risk of bias and the data to be included in the meta-analysis to avoid data overlap.…”
Section: Study Selectionmentioning
confidence: 99%
“…15 The manufacturer states that the incorporation of nanosized filler particles can improve compressive strength and wear resistance. 16,17 When this product was tested as a pit and fissure sealant controversial results have been reported [18][19][20][21][22] in comparison to resin-based and/or glass ionomer cement.…”
Section: Introductionmentioning
confidence: 99%
“…Hu ve ark. 41 yaptıkları çalışmada yüksek viskoziteli CİS, cam karbomer ve rezin esaslı fissür örtücülerin 2 ve 3 yıl sonraki retansiyon durumlarını değerlendirmiş, retansiyon kaybı olan dişlerdeki fissür örtücü kalıntılarını SEM ile incelemiştir. Klinik olarak incelendiğinde, retansiyon kaybı olan dişlerde, fissür örtücü kalıntıları arasında farklılık gözlenmezken, SEM incelemesinde de 2 ve 3 yıl sonrası gözlemde CİS fissür örtücü kalıntılarının cam karbomer ve rezin esaslı fissür örtücü kalıntılarından fazla olmadığı gözlenmiştir.…”
Section: Cam Karbomerunclassified